ANALISIS HASIL UKK MATEMATIKA SISWA KELAS VIII MTs NEGERI 1 RAKIT BANJARNEGARA - Zuhrotunnisa Zuhrotunnisa (AlphaMath : Journal of Mathematics Education, 2016)
ABSTRACT: This research is aimed to analyze the result of the last semester evaluation the eight grade students of MTs N. 1 Rakit Banjarnegara. The sample of this research is taken from three classes among six classes in MTs N 1 Rakit. They are from VIII A, B and D by using purposive sampling technique. They are the students from the high class (VIIIA), medium class (VIII B) and the low class (VIII D). Based on the analysis of the last semester evaluation can be concluded that: (1) the students from the high class can comprehend all of the basic competence (KD) with the percentage 87,27%; (2) the students from the medium class for multiple choice test can comprehend only KD 5.1 and KD 5.2, and the for essay test can comprehend KD 4.2 and KD 4.3; (3) the result of the students from the medium class can comprehend 52,79%; (4) the students from the low class for multiple choice test can comprehend only KD 5.2, and the for essay test can comprehend all of the basic competence (KD), the achievement of each KD is 60%; (5) the precentage of KD attainment from the students of the low class is 46.35 %. KEY WORDS: Analysis, the last semester evaluation